Franceschetti syndrome - Vikrant Kasat (Wolters Kluwer Medknow Publications, 2011)
Franceschetti syndrome is an autosomal dominant disorder of craniofacial development with variable expressivity. It is commonly known as Treacher Collins syndrome (TCS). It is named after E. Treacher Collins who described the essential components of the condition. It affects both genders equally. This article reports a case of TCS in an 18-year-old female.